Litery są – czyli o roli projektanta krojów pisma w projektowaniu książki - Jarzec, Robert (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
This article analyses the role and significance of the typeface designer in the book design process. It discusses the characteristics of this profession from its historical roots in calligraphy and lettering, through the typographic printing period and phototypesetting up to the digital era. This is followed by an outline of the evolution of the profession in the context of technological and cultural changes, with particular interest in the impact of the designer on the readability and aesthetics of the publication. The article also presents the contemporary typographic landscape, including the democratisation of the processes of publication design and typeface distribution, with the resulting challenges. The text emphasises the role of typeface designers in the communication process, linking the technical aspects with the aesthetic and functional ones.